Pernikahan Dini dan Implikasinya dalam Hukum Ekonomi Syariah: Studi Kasus Kecamatan Dendang: Penelitian - Andre Setyo Bayu; M. Arif Musthofa; Zeni Sunarti; Wargo; Sayida Khoiratun Nisak (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine and analyze public perceptions of early marriage practices from the perspective of Islamic Economic Law in Dendang District. This study uses a descriptive method with a qualitative approach, where data collection techniques are carried out through observation, interviews, and documentation. Primary data sources were obtained directly from the results of field observations and interviews with various informants involved in early marriage practices, such as community leaders, parents, and local religious officials. The results of the study indicate that early marriage practices still occur widely in Dendang District, with several main factors as drivers, including weak economic conditions, low levels of education and knowledge of parents and children, and the strong influence of culture and tradition that encourage parents to marry their children at a young age. In addition, the urge to avoid promiscuity and concerns about the potential for adultery are also the main reasons for early marriage. Based on the views of the community, the practice of early marriage is considered quite good as long as it can prevent children from acts that violate religious and social norms. However, from the perspective of Islamic Economic Law, early marriage without mature economic readiness and responsibility is considered to not fulfill the principles of maslahah (benefit), adl (justice), and amanah (responsibility).